Analisis Minat Belajar Pada Siswa SMP Al-Qur’an Wahdah Islamiyah Cibinong: Analysis of Learning Interest among Students at Wahdah Islamiyah Qur’anic School Cibinong - Iskandar, Iskandar; Samsuddin, Samsuddin; Agusman, Agusman; Suratman Trias Ramli (Litera Academica Publishing, 2026)
This study aims to examine the level and characteristics of learning interest among students at SMP Al-Qur’an Wahdah Islamiyah Cibinong and to identify the factors influencing it. The research employed a quantitative method with a descriptive approach, involving 43 students aged 12–17 years and using a questionnaire adapted from Darmadi’s learning interest scale, covering indicators of enjoyment, interest, attention, and involvement. The findings indicate that students’ learning interest falls within the moderate or fairly good category, with an empirical mean score of 124.79. Indicators of enjoyment, interest, and involvement were categorized as high, while students’ attention was moderate. These results suggest that students have a positive learning interest, particularly in affective and behavioral dimensions, but there is still room for improvement, especially in enhancing attention during learning. The study provides both theoretical and practical contributions by guiding schools to develop integrative, interactive, and value-based learning strategies, foster motivation, and create a supportive learning environment aligned with Islamic education principles, promoting lifelong learning.